2014
DOI: 10.5194/piahs-364-507-2014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms optimization of hedging rules for operation of the multi-purpose Ubonratana Reservoir in Thailand

Abstract: This study has developed optimal hedging policies for the multi-purpose Ubonratana Reservoir in northeastern Thailand based on its existing rule curves. The hedging policy was applied whenever the reservoir storage falls below a critical level for each month of the year. The decision variables, i.e. the set of monthly storages defining the critical rule curve that triggers rationing and the rationing ratio, were optimized by genetic algorithm (GA). Both single stage (i.e. with one critical rule curve and one r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Chiamsathit used optimal hedging policies for the operation of Ubonratana Reservoir in Thailand. The output results showed that the vulnerability was significantly reduced by using the optimized hedging rules [31].…”
Section: Discussionmentioning
confidence: 99%
“…Chiamsathit used optimal hedging policies for the operation of Ubonratana Reservoir in Thailand. The output results showed that the vulnerability was significantly reduced by using the optimized hedging rules [31].…”
Section: Discussionmentioning
confidence: 99%
“…Critical curves CR 1 and CR 2 define the storage values, which are triggers for rationing in the associated proportion. It was noted that the rationing is done in two stages and that the rationing factors in the supply demand, α 1 and α 2 , meet the 0 ≤ α 2 ≤ α 1 ≤ 1 condition (Chiamsathit et al, 2014).…”
Section: Proposed Scenariosmentioning
confidence: 99%
“…The standard operating policy (SOP) is the simplest and most often-used reservoir policy: that if possible, only the amount of water required in each period be released so that water can be preserved for future requirements (Rittima, 2009). However, SOP is not the ideal policy for reservoir operation because it causes large, single-period shortage or vulnerability (Chiamsathit et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, there have been many different ways of water supply operating rule curves, such as the standard operation rule curve [5], in which the release of the reservoir is a function of total available water (reservoir storage plus the inflow), and the hedging rule curve [6][7][8], in which the possibility of a drought event can occur in the future. The most challenging aspect of hedging is determining the timing and amount of rationing, as failing can be detrimental.…”
Section: Introductionmentioning
confidence: 99%